DIMITRI VANOVERBEKE, Community and State in the Japanese Farm Village: Farm Tenancy Conciliation (1924-1938) - Nottage, Luke (Zeitschrift für Japanisches Recht, 2004)
DIMITRI VANOVERBEKE Community and State in the Japanese Farm Village: Farm Tenancy Conciliation (1924-1938) Leuven University Press (Leuven, Belgium, 2004) 200 pp.; ISBN 90 5867 307 3